Analysis of the Mermule Tradition and Visit of Mbah Buyut Tambi, Tambi Village, Sliyeg District, Indramayu Regency - Didik Himmawan; Tri Ulfah Nurjanah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Tomb of Mbah Buyut Tambi is a historical and religious site with unique and sacred traditions, such as